The Impact of Environmental Policies on the Sustainable Development of the Southeast Region - Maria Magdalena Turek Rahoveanu; Adrian Turek Rahoveanu; Gheorghe Adrian Zugravu; Laura Constanta Zugravu (Journal of Agriculture and Rural Development Studies)
The purpose of this research is to assess the implementation of environmental policies in the South-East Region, taking into account the differences between counties that influence development. From a methodological point of view, using the Spearman correlation coefficient, the implementation of environmental policies was assessed through 6 environmental indicators selected and prioritized at the level of the 6 counties, with the use of the Tempo online database. The research results fall within the current guidelines of the 8th EAP, which analyzed the performance of environmental policies in the region, in the analyzed period 2006-2020, as well as the proposed measures for environmental management in the following period.